Respiratory Insufficiency Scale Validity in Patients with Acute Neural Lesion - M. B. Nazarenko; K. V. Kiselyov; E. I. Shchedrina; A. B. Kalmykov; N. M. Kruglyakov; O. V. Parinov; Y. D. Udalov; M. V. Zabelin; A. S. Samoylov; K. A. Popugayev (Неотложная медицинская помощь)
The aim of study: to investigate validity of respiratory insufficiency scale (RIS) in patients with acute lesions of nervous system.Material and methods. The prospective observational study included neurocritical care patients (n=179), admitted to the resuscitation and intensive care unit with independent breathing and RIS score 1 and higher. Patients were assessed according to RIS every 12 hours during the the period of RICU stay until the beginning of artificial lung ventilation or transfer to a specialized department. The RIS score did not influence the physician's decision upon intubation. The treatment was performed in accordance with national and international recommendations.Depending on the tracheal intubation and ALV, patients were divided into 3 groups. Group I (n=65): 0% tracheal intubation and ALV; Group II (n =54): 42,6% cases of intubation and ALV; Group III (n=60): 100% patients requiring intubation and ALV.The statistical analysis was performed using Shapiro—Wilk test, Mann-Whitney test, Kruskal—Wallis test, Chi-squared test. The ROC analysis was carried out to determine the sensitivity and specificity of the RIS scale.Results. Patients with RIS score 1 — 2 did not require intubation and ALV. Patients with RIS 5 or more required urgent intubation and ALV. In patients with RIS score 3—4 the need for intubation and ALV was unpredictable. If RIS score 4 was sustainig during several hours, or if increased from 3 to 4, a patient required intubation and initiation of ALV.Conclusion. RIS helps objectify indications for intubation and ALV in patients with acute neural lesions.